The development of equipment for the fabrication of thin film superconductor and nano structures - Buttner, Ulrich (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2011.